Digital Data Preservation for Scholarly Publications in Astronomy - Sayeed Choudhury; Tim DiLauro; Alex Szalay; Ethan Vishniac; Robert Hanisch; Julie Steffen; Robert Milkey; Teresa Ehling; Ray Plante (International Journal of Digital Curation, 2008)
Astronomy is similar to other scientific disciplines in that scholarly publication relies on the presentation and interpretation of data. But although astronomy now has archives for its primary research telescopes and associated surveys, the highly processed data that is presented in the peer-reviewed journals and is the basis for final analysis and interpretation is generally not archived and has no permanent repository. We have initiated a project whose goal is to implement an end-to-end prototype system which, through a partnership of a professional society, that society’s scholarly publications/publishers, research libraries, and an information technology substrate provided by the Virtual Observatory, will capture high-level digital data as part of the publication process and establish a distributed network of curated, permanent data repositories. The data in this network will be accessible through the research journals, astronomy data centers, and Virtual Observatory data discovery portals.